`1/(cos(x) + 1) + 1/(cos(x) - 1) = -2csc(x)cot(x)` Verify the identity.

Asked on by enotes

Textbook Question

Chapter 5, 5.2 - Problem 31 - Precalculus (3rd Edition, Ron Larson).
See all solutions for this textbook.

2 Answers | Add Yours

mathace's profile pic

mathace | (Level 3) Assistant Educator

Posted on

Verify the identity: `1/(cos(x)+1)+1/(cos(x)-1)=-2csc(x)cot(x)`



Use the pythagorean identity `sin^2(x)+cos^2(x)=1` to simplify the denominator.

If `cos^2(x)-1`   is isolated the equation would be `cos^2(x)-1=-sin^2(x).`




Use the reciprocal identity csc(x)=1/sin(x). Also use the quotient identity cot(x)=cos(x)/sin(x).


balajia's profile pic

balajia | College Teacher | (Level 1) eNoter

Posted on

By cross multiplication ,we get

`1/(cosx+1)+1/(cosx-1) = (cosx-1+cosx+1)/(cos^2x-1)`




We’ve answered 319,670 questions. We can answer yours, too.

Ask a question